Endoscopic ultrasound-guided gallbladder drainage, transpapillary drainage, or percutaneous drainage in high risk acute cholecystitis patients: a systematic review and comparative meta-analysis - Mohan, Babu P.; Khan, Shahab R.; Trakroo, Sushruth; Ponnada, Suresh; Jayaraj, Mahendran; Asokkumar, Ravishankar; Adler, Douglas G. (Endoscopy, 2020)
Background Endoscopic transpapillary gallbladder drainage (ETGBD) and endoscopic ultrasound-guided gallbladder drainage (EUSGBD) are alternatives to percutaneous gallbladder drainage (PCGBD) for patients with acute cholecystitis who are unfit for surgery. Data comparing these modalities are limited and have reported conflicting results.Methods We searched multiple databases from inception to May 2019 to identify studies that reported on ETGBD, EUSGBD, and PCGBD in the management of acute cholecystitis in patients with a high surgical risk. Aims were to compare the pooled rates of technical success, clinical success, adverse events, and disease recurrence.Results 1223 patients (22 studies), 557 patients (14 studies), and 13 351 patients (46 studies) were treated by ETGBD, EUSGBD, and PCGBD, respectively. The pooled technical and clinical successes were: ETGBD 83 % (95 % confidence interval [CI] 80.1 – 85.5, I2 = 29) and 88.1 % (95 %CI 83.6 – 91.4, I2 = 50), respectively; EUSGBD 95.3 % (95 %CI 92.8 – 96.9, I2 = 0) and 96.7 % (95 %CI 94.0 – 98.2, I2 = 0), respectively; and PCGBD 98.7 % (95 %CI 98.0 – 99.1, I2 = 0) and 89.3 % (95 %CI 86.6 – 91.5, I2 = 84), respectively. Clinical success with EUSGBD was significantly superior to the other approaches. All complications were comparable between the groups. Pancreatitis occurred with ETGBD in 5.1 % (95 %CI 3.5 – 7.3), whereas bleeding and perforation occurred with EUSGBD in 4.3 % (95 %CI 2.7 – 6.8) and 3.7 % (95 %CI 2.3 – 6.0), respectively. Stent migration occurred with PCGBD in 7.4 % (95 %CI 5.5 – 10.0).Conclusion EUSGBD demonstrated better clinical success than ETGBD and PCGBD in the management of acute cholecystitis patients at high surgical risk.